First in the Family to Attend University: Understanding and Enabling the Parent-child Support Relationship - Apps, Joanna; Christie, Sarah (International Journal about Parents in Education, 2023)
There is very little qualitative research on parental support around transition to university in the UK. The objective of this study was to explore how parents who have not been to university support their children in making decisions about, and transitions to, university. Thirty in-depth interviews were conducted with parents and students (aged 16-18 years) from three schools, who would be the first in their family to go to university (FIFU). Parents and young people reported discussing whether they would go to university, what to study and where to go over a long period of time, as part of everyday activities. The emotional impact of children leaving home to go to university influenced how parents felt about their child’s decisions to go, along with being unable to envisage what being at university would be like for their children. Parents often found online information confusing and not relevant to their child. They reported receiving little information from schools. Parents lacked basic information and sought answers from friends and colleagues with any experience of higher education. Parents most wanted personalised information, signposting to online resources and a timetable of what they needed to do to support their children’s applications to university. The results are framed in terms of the cultural capital available to these parents and young people.